Sufentanil increases delirium risk compared to fentanyl in elderly perioperative ischemic stroke patients: a retrospective cohort study - He, Yanan; Qu, Mengyao; Song, Yuxiang; Wang, Rui; Li, Peng; Li, Yingfu; Lu, Yixun; Sun, Miao; Yang, Huikai; Guo, Hang; Mi, Weidong; Ma, Yulong (Frontiers in Medicine, 2026)
BackgroundPerioperative ischemic stroke (PIS) and postoperative delirium (POD) are each serious central nervous system complications. When they occur together, they present a potentially devastating but largely understudied condition. Evidence on risk factors for this combined pathology is scarce. This study examined the incidence and prognosis of PIS complicated by POD and evaluated whether intraoperative opioid choice, fentanyl versus sufentanil, affects the risk of this dual complication.MethodsWe retrospectively analyzed 376,933 patients who underwent non-cardiac surgery between January 2008 and August 2019. After applying exclusion criteria, 525 patients with PIS were identified. Of these, 178 elderly patients (≥ 65 years) formed the study cohort. Kaplan–Meier survival curves were used to compare overall survival between patients with and without POD, with group differences assessed by the log-rank test. Patients were categorized into a fentanyl group (n = 73) and a sufentanil group (n = 105). The primary outcome was POD within 7 days after surgery. Multivariate logistic regression examined the association between opioid type and POD risk, adjusting for patient- and surgery-related confounders. Additionally, 1:1 propensity score matching (44 matched pairs) was used to balance baseline characteristics and confirm findings.ResultsThe overall POD incidence among elderly PIS patients was 40.4% (72/178). Patients who developed POD had obviously worse survival compared to those who did not (30% vs. 50%). The incidence of POD was markedly lower in the fentanyl group than in the sufentanil group (6.8% vs. 63.8%). Fully adjusted models showed fentanyl use was associated with a substantially reduced risk of POD (OR: 0.017, 95% CI: 0.003–0.070, p < 0.001). The lower POD risk with fentanyl compared to sufentanil remained consistent across subgroups stratified by age, sex, and diabetes status.ConclusionIn elderly patients with PIS, intraoperative fentanyl use was associated with a significantly lower risk of POD compared with sufentanil. Opioid selection may represent a modifiable risk factor in this high-risk population, offering an opportunity to improve anesthetic management and postoperative outcomes.